Effects of Graphene Oxide and Reduced Graphene Oxide on the Mechanical and Dielectric Properties of Acrylonitrile-Butadiene Rubber and Ethylene-Propylene-Diene-Monomer Blend - Bismark Mensah; David Sasu Konadu; Benjamin Agyei-Tuffour (International Journal of Polymer Science)
The composites of properties of ethylene-propylene-diene-monomer (E) and acrylonitrile butadiene-rubber (N) composites of graphene oxide (GO) and reduced graphene oxide (G) were prepared by a combination of solution and open-roll method. They include single matrices (EGO and EG) and blends N/E, 20 part of hundreds of rubber (phr)/80 phr (A), 80 phr/20 phr (B), and 50 phr/50 phr(C) blend containing GO and G. The physico-mechanical properties including vulcanization, tensile, glass transition temperature (Tg), and dielectric spectroscopic properties were evaluated. The N-rich systems reinforced with GO, cured faster than the E-rich systems. Also, N-rich systems obtained the highest dielectric constant ɛ′, especially when GO and G were incorporated, for example, NG and N-GO obtained 317 and 283% increment in ɛ′ than EG and EGO, respectively. In terms of tensile properties, AGO exhibited the highest strength and elongation at break properties (%). Therefore, solution mixing technique of rubber blends filled with nanoinclusion can be achieved with the tendency of reducing cost without the use of compatibilizer and still maintain the integrity of the physical properties of the final product. The result obtained therefore shows that the current compositions can find various applications in oil/gas sealants, heat-resistant applications, and energy storage materials with minimal losses.